A qualitative meta-analysis of intercultural research into audio-visual synchronous communication between language learners - Begoña Clavel-Arroitia; Barry Pennock-Speck (Revista de Lingüística y Lenguas Aplicadas)
In this article we conduct a meta-analysis (Timulak, 2009) of qualitative studies into computer-mediated, synchronic, oral interactions between language learners from different countries focusing primarily on Intercultural Communicative Competences (ICCs) (Byram, 1997). To find studies that met our criteria, keyword searches were conducted in Google Scholar and in the main CMC journals. To filter the search results, we used AntConc 4.4, and close readings of the studies found. We ascertained that only three met our criteria (O’Dowd, 2006; Akiyama, 2017; Liaw, 2019). Our analysis shows that the ICCs identified in these articles are also found intraculturally. Moreover, when the language competence of the participants is similar, we argue that the communication between NS and NNS is practically indistinguishable from NS-to-NS communication. These results seem to call into question the validity of ICCs. We conclude therefore that language teaching should focus on improving communicative and pragmatic competence in the target language.